Experimental study on film thickness and the problem of free surface film flow in dip coating. Issue 5 (6th April 2016) - Chen, Meng Meng; Zhang, Xian Ming; Ma, Jian Ping; Chen, Shi Chang; Chen, Wen Xing; Feng, Lian Fang
Abstract: Dip coating is widely applied in industries for coating a solid substrate with a fluid because of its simplicity and applicability to substrates with different shapes. An experimental study was reported with dip coater on the film coating of solid plates by withdrawal from a tank filled with silicone oil fluids or polyacrylic acid (PAA) solutions with different rheological properties, the liquid film thickness deposited on the plate substrate was measured using capacitance method, and the evolution of free surface morphology was recorded with photographs. The purpose was to investigate the effects of plate substrate roughness, withdrawal speed, rest time, and fluid viscosity on the liquid film thickness and free surface morphology in detail. Results showed that the increases in coating fluid viscosity, withdrawal speed, and substrate roughness are beneficial to film thickening. The influence of rest time on liquid film thickness could be neglected when it was greater than 3 min. For silicone oil fluids, the free surface exhibited a depression, which gradually deepened, with the increasing in withdrawal speed and viscosities. By contrast, PAA solutions showed a bump on the free surface, exhibiting a curvature that increased with the increasing in withdrawal speed and concentrations. © 2016 Curtin University of Technology and John Wiley & Sons, Ltd.